2017
DOI: 10.1186/s12864-017-3589-6
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Groucho-mediated repression revealed by genome-wide analysis of Groucho binding and activity

Abstract: BackgroundThe transcriptional corepressor Groucho (Gro) is required for the function of many developmentally regulated DNA binding repressors, thus helping to define the gene expression profile of each cell during development. The ability of Gro to repress transcription at a distance together with its ability to oligomerize and bind to histones has led to the suggestion that Gro may spread along chromatin. However, much is unknown about the mechanism of Gro-mediated repression and about the dynamics of Gro tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 98 publications
(108 reference statements)
4
20
0
Order By: Relevance
“…The genomic distribution of TLE3 mapped principally to distal regions of the mouse genome ( Fig. 5C), an observation that is consistent with the TLE/Groucho family being located primarily at enhancers (Chambers et al 2017;Dali et al 2018). There was nearly equal distribution of binding upstream of and downstream from the transcriptional start site (TSS) (Supplemental Fig.…”
Section: Tle3 Promotes Diet-induced Weight Gain and Glucose Intolerancesupporting
confidence: 68%
“…The genomic distribution of TLE3 mapped principally to distal regions of the mouse genome ( Fig. 5C), an observation that is consistent with the TLE/Groucho family being located primarily at enhancers (Chambers et al 2017;Dali et al 2018). There was nearly equal distribution of binding upstream of and downstream from the transcriptional start site (TSS) (Supplemental Fig.…”
Section: Tle3 Promotes Diet-induced Weight Gain and Glucose Intolerancesupporting
confidence: 68%
“…The genomic distribution of TLE3 mapped principally to distal regions of the mouse genome ( Figure 5C), an observation that is consistent with the TLE/Groucho family being located primarily at enhancers (37,38). There was nearly equal distribution of binding upstream and downstream of the transcriptional start site (TSS) ( Figure S5A).…”
Section: Genome-wide Analysis Reveals Preferential Association Of Tlesupporting
confidence: 58%
“…For example, not only is Pnt essential for proper Yan occupancy, but it also recruits the co-repressor Gro to the same set of regulatory elements. Prior genome-wide analyses of Gro occupancy and function in embryos and cultured cells have shown that Gro-regulated genes are enriched for epigenetic marks and promoter proximal transcripts commonly associated with paused RNA pol II (Kaul et al, 2014;Chambers et al, 2017). Our demonstration of eve de-repression in embryos doubly heterozygous for gro and Trl provides the first genetic evidence of a possible direct mechanistic link between Gro repressive complexes and the RNA pol II pausing machinery.…”
Section: Discussionmentioning
confidence: 63%